2012
DOI: 10.1016/j.jpubeco.2012.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Consumption, retirement and social security: Evaluating the efficiency of reform that encourages longer careers

Abstract: This paper proposes and analyzes a Social Security reform in which individuals no longer face the OASI payroll tax after, say, age 54 or a career of 34 years, and their subsequent earnings have no bearing on their benefits. We first estimate parameters of a life–cycle model. Our specification includes non-separable preferences and possible disability. It predicts a consumption–expenditure change at retirement. We use the magnitude of the expenditure change, together with households’ retirement–age decisions, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
46
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 47 publications
1
46
0
Order By: Relevance
“…To provide a few examples, Song and Manchester (2007), Mastrobuoni (2009), andCoe, Kahn andRutledge (2013) examine the effects of changing the full retirement age using cohort differences. Laitner and Silverman (2012) examine the effects of increasing the payroll tax in a basic life cycle model. Coile, Diamond et al (2002) examine claiming outcomes.…”
mentioning
confidence: 99%
“…To provide a few examples, Song and Manchester (2007), Mastrobuoni (2009), andCoe, Kahn andRutledge (2013) examine the effects of changing the full retirement age using cohort differences. Laitner and Silverman (2012) examine the effects of increasing the payroll tax in a basic life cycle model. Coile, Diamond et al (2002) examine claiming outcomes.…”
mentioning
confidence: 99%
“…Livshits, MacGee, and Tertilt (2007), Attanasio, Low, and SanchezMarcos (2008) set δ(N t ) = 1 such that in each period the household planer maximizes per-capita utility or alternatively the household planer does not have any altruism towards the remaining household members. Fuchs-Schündeln (2008) and Laitner and Silverman (2012) Heathcote, Storesletten, and Violante (2012) use the number of adults in the household and Domeij and Klein (2012) the total number of household members. Attanasio, Banks, Meghir, and Weber (1999), and Gourinchas and Parker (2002) employ CRRA preferences and use a more general taste…”
Section: Demographics Modelmentioning
confidence: 99%
“…His work provided some preliminary evidence that claiming probabilities could rise in response. Fetherstonhaugh and Ross (1999) reported that for 80 percent of their survey respondents, a lump-sum payment instead of an increase in annual benefit amounts due to delayed claiming 1 See Feldstein and Leibman (2002) for a review, and most recently, Laitner and Silverman (2012). 2 See Kotlikoff and Viceira (2008), Chai, Horneff, Maurer, andRogalla (2012).…”
Section: Prior Studiesmentioning
confidence: 99%